Consensus Statement on the Outcome of the European Herbal Health Products Summit – Which Way Forward? - Heinrich, Michael; Reiken, Babette; Roether, Bernd; Müller, Angela; Rumsch, Julia; Symma, Nico (Planta Medica, 2024)
Herbal medicinal products are a vital part of the healthcare system in Europe and beyond. Being predominantly sold as non-prescription medicines in pharmacies, they are very popular with patients, physicians, and pharmacists and are therefore an important part of self-medication. Interest in this sector has recently gained momentum, reflecting the ongoing revision of the general pharmaceutical legislation and the recent discussion on nutrition and health claims on foods based on the implementation report of Regulation (EC) No 1924/2006 by the European Parliament 1. Therefore, on 20th February 2024, the Society for Medicinal Plant and Natural Product Research (GA), in collaboration with the German Pharmaceutical Industry Association (BPI) and the German Medicines Manufacturersʼ Association (BAH, now Pharma Deutschland), hosted an in-person summit in Brussels entitled ‘European Herbal Health Products Summit – Which way forward?ʼ. The summit featured a wide range of speakers, including policymakers, regulatory authorities, industry representatives, and academic experts. It was divided into several sessions covering topics such as the future and relevance of herbal medicinal products in the EU, the revision of the EU pharmaceutical legislation, and the resulting impact on herbal medicinal products. Furthermore, the discussions delved into the “Health Claims Regulation” – the European Parliamentʼs implementation report and the related regulatory challenges of herbal medicinal products at an EU level. This consensus paper summarises the current status and provided recommendations to pave the way for future strategies to ascertain the continued use of herbal medicinal products as an important therapeutic option for patients.
Keywords: herbal medicinal products; herbal medicines; botanicals; EU pharmaceutical legislation; health claims